Interaction in English as a Foreign Language Classroom (A Case of Two State Senior High Schools in Semarang in the Academic Year 2009/2010) (English Education Journal, 2011)
The word interaction, in the era of communicative languageteaching, seems to be very important for language teachers since thisis, in fact, the heart of communication and this is also whatcommunication is all about. Through interaction teachers are enabledto do various jobs for the success of their language teaching.Teaching language is not only a matter of transferring knowledge butthis is also a matter of how to make students understand about usingthe target language correctly either actively or passively as what hasbeen demanded by nowadays competitive era.Teaching English as a foreign language at senior high schoolseems to be challenging since the targets of the teaching seem to bedifferent from those, at any levels bellow. One of the teaching targetsinsists the institutions to prepare their graduates to face the realworld after school. Hence the jobs held by institutions at this levelare no longer easy. Such phenomenon triggers me to conduct a studyand focus on the classroom interaction among teacher and studentsin state senior high school in Semarang. The main objectives of theproposed study were to find out the amount of time spent by teacher(TTT) and by students (STT) and to find out the characteristics ofclassroom interaction in two senior high school, EFL classes inaddition to finding out the relation between statement of the problemone and two, using FIAC. The study involved students and teachersof SMAN 3 Semarang and SMAN 6 Semarang in the academic year2009/2010 as the object of the study.In detail, the first result of analysis showed that the teacherspent 45.9% of the classroom available time, meanwhile the studentstook 54.1% of the available time during the interaction in SMAN 3.Meanwhile, during the interaction in SMAN 6 Semarang teacher took49.7% of the classroom available time while the students only took49.5% of the available time. However the amount of student talkingtime, found at 54.1% (SMAN 3) and at 49.5% (SMAN 6) did notrepresent the actual amount of talk performed by each student in theclassrooms. In this case, it should be less than 49.5% since this amount was found to be the total amount of talk time performed bythe students during the classroom interactions. Therefore it wasinferred that English teaching and learning process in both seniorhigh schools were teacher centered. The second result of analysisshowed that the general characteristics of classroom interactionfound in both state senior high schools encompassed content cross,student participation, student talking time (STT), indirect ratio whichwas differentiated by the different number of percentage, teachertalking time (TTT), teacher support, teacher control and period ofsilence. And the third result of this analysis showed thatcharacteristic of classroom interaction was significantly influenced bythe type of talking time performed by teachers and students duringthe interaction.At last, this study was significant because its findings andconclusions may stimulate teachers to improve their teaching behavior inorder to maximize student learning.